2007
DOI: 10.1165/rcmb.2007-0099oc
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Presenting Cell Population Dynamics during Murine Silicosis

Abstract: Silicosis is an occupational lung disease resulting from the inhalation of silica particles over prolonged periods of time, which causes chronic inflammation and progressive pulmonary fibrosis. Alveolar macrophages (AM) are critical effector cells, while less is known about the role and function of pulmonary dendritic cells (DC) in silicosis. We hypothesize that a balance exists between the suppressive nature of AM and the stimulatory capacity of DC to regulate lung immunity, and that this equilibrium may be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 55 publications
5
28
0
Order By: Relevance
“…Lung macrophages that outnumber stimulatory DCs at steady state have been shown to inhibit DC antigen presentation and airway hyperresponsiveness in vivo (35)(36)(37)(38). The inversion of the ratio of lung macrophages to DCs observed in our study has been observed in a murine model of silicosis (39) and in an even more relevant human study of inhalational LPS (40), suggesting that the balance between these myeloid populations may play a critical role in the development of other environmental lung diseases. However, the associations between APCs, the persistence of proinflammatory responses, and the physiologic responses we report have not been previously described, to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 58%
“…Lung macrophages that outnumber stimulatory DCs at steady state have been shown to inhibit DC antigen presentation and airway hyperresponsiveness in vivo (35)(36)(37)(38). The inversion of the ratio of lung macrophages to DCs observed in our study has been observed in a murine model of silicosis (39) and in an even more relevant human study of inhalational LPS (40), suggesting that the balance between these myeloid populations may play a critical role in the development of other environmental lung diseases. However, the associations between APCs, the persistence of proinflammatory responses, and the physiologic responses we report have not been previously described, to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 58%
“…They concluded that reactive oxidant activation as a consequence of various sources of particulate matter is cell specific, and that the inflamed lung is more susceptible to harm from a broader range of particulate size and composition because of the oxidant stress posed. 138 In response to silica exposure, Beamer and Holian found that large numbers of granulocytes were recruited to the lungs of C57Bl6 mice, 139 consistent with the findings of Becker et al 138 They also noted that the alveolar macrophage to dendritic cell ratio was noticeably altered in favor of dendritic cells in response to silica compared to unexposed mice, though a subset population of inflammatory CD11b high alveolar macrophages appeared. Beamer and Holian suggested silica-induced apoptosis of alveolar macrophages as one explanation of their decrease in numbers with time subsequent to silica exposure, 139 though their observation of macrophage migration to the interstitium (and other observations 115 ) is an additional explanation.…”
Section: Toxicological Consequences Of Metallo-particle Inhalation Spsupporting
confidence: 67%
“…An in vivo study using mice reached a similar conclusion as the normal immune suppressive AM population was replaced by immune active dendritic cells (DC) following silica instillation. Further evidence in this study showed that DC preferentially migrated to the lung parenchyma from the alveoli increasing the numbers of activated T lymphocytes in response to silica [110]. Davis et.…”
Section: The Role Of Silica Exposure In Macrophage Immune Dysfunctionmentioning
confidence: 51%